INTEGRATION OF ACTIVE METHODOLOGIES AND ARTIFICIAL INTELLIGENCE IN TEACHING SEQUENCES AND SERIES: A CLASSROOM EXPERIENCE IN A BLENDED COURSE AT THE COSTA RICA INSTITUTE OF TECHNOLOGY - Acuña Chacón, Acuña Chacón (2025)
This work describes an educational experience developed in a college Calculus course, focused on the study of sequences and series. Two active methodologies were implemented in order to strengthen the conceptual and practical understanding of those topics: Just-in-Time Teaching (JiTT) and Peer Instruction (PI), both supported by Artificial Intelligence (AI) tools Two groups were compared: an experimental group, which integrated these methodologies with AI, and a control group, with a traditional approach. The results showed improvements in mathematical reasoning, collaboration and academic performance in the experimental group. This experience, in addition to being replicable, highlights the potential of integrating active methodologies and emerging technologies in university mathematics education, in accordance with international trends.